2019
DOI: 10.1007/s10973-019-08594-x
|View full text |Cite
|
Sign up to set email alerts
|

Thermal, spectroscopic, X-ray and theoretical studies of metal complexes (sodium, manganese, copper, nickel, cobalt and zinc) with pyrimidine-5-carboxylic and pyrimidine-2-carboxylic acids

Abstract: The new 3d metal complexes of pyrimidine-2-carboxylic (2PCA) and pyrimidine-5-carboxylic (5PCA) acids were synthesized and characterized using thermal analysis (TG-DSC, TG-FTIR), X-ray, spectroscopic (IR, Raman) methods and theoretical (DFT) studies. In the complexes of pyrimidine-2-carboxylic acid of the general formula M(2PCA) 2 ÁxH 2 O (where 2PCA-pyrimidine-2-carboxylate; M = Mn(II), Co(II), Ni(II), Cu(II) and Zn; x = 0 for Mn and Cu; x = 2 for Co, Ni and Zn) coordination of metal ions occurs through nitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 58 publications
1
8
0
Order By: Relevance
“…Variation in both the temperature and number of steps were apparent for the subsequent weight losses of Th‐1 and Th‐2 . These differences in the thermal decomposition temperature and profiles of the 2‐furoate and 3‐furoate bridged chains are consistent with literature reports that have shown that the position of the carboxylate leads to differences in the thermal stability of carboxylic acids and also potentially highlight the impact that supramolecular interactions have on the properties of metal‐organic phases. Unfortunately, the incomplete refinement of Th‐1 precludes a more in‐depth analysis of the possible correlation between packing interactions and differences in the thermal stabilities of Th‐1 and Th‐2 .…”
Section: Resultssupporting
confidence: 90%
“…Variation in both the temperature and number of steps were apparent for the subsequent weight losses of Th‐1 and Th‐2 . These differences in the thermal decomposition temperature and profiles of the 2‐furoate and 3‐furoate bridged chains are consistent with literature reports that have shown that the position of the carboxylate leads to differences in the thermal stability of carboxylic acids and also potentially highlight the impact that supramolecular interactions have on the properties of metal‐organic phases. Unfortunately, the incomplete refinement of Th‐1 precludes a more in‐depth analysis of the possible correlation between packing interactions and differences in the thermal stabilities of Th‐1 and Th‐2 .…”
Section: Resultssupporting
confidence: 90%
“…The stretching vibration of CN in the pyrimidine ring (1568 cm −1 ) shifted to a lower wavenumber when APC was mixed with PbI 2 . 30 This is attributed to the interaction between APC and Pb 2+ , where the pyrimidine N atoms donated their unpaired lone electrons to the empty orbitals of Pb 2+ . A similar shift for the APC-FAI mixed sample confirmed that APC could interact with both PbI 2 and FAI (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our studies showed that there is a dependency between the electronic charge distribution in metal complex and salt molecules and the location of these metals in the periodic table [20]. Alkali metal cations and some heavy metal cations (Ag(I), Pb(II), Hg(I), Hg(II)) perturb the electronic system of ligands (benzoic, salicylic, pyridinecarboxylic acids and others), whereas 3d and 4f metal cations stabilize it [21][22][23][24][25][26]. This conclusion allows us to foresee the changes in the electronic structure under the influence of metal cations and estimation of the physicochemical and biological properties of complexes.…”
Section: Introductionmentioning
confidence: 99%